On Listening Teaching of TCFL and Cultivating the Ability of Listening and Speaking - Sun, Y; Lei, J (KnE Social Sciences, 2018)
Listening is an essential part of TCFL, but, listening class should not be just limited to listen and doing listening exercises, it should combine hearing training and verbal training and should focus on cultivating students’ language-thinking ability. What it teaches should be flexible to make teaching live and practical. Keywords: TCFL, listening teaching, ability of listening and speaking